DINASTI FATIMIYAH : ANALISIS KEMAJUAN DAN RUNTUHNYA PERADABAN ISLAM DI MESIR - irwan supriadin j (STIT Sunan Giri Bima, 2021)
This article intends to present an analysis of the progress and decline of the Fatimid dynasty, and their impact on Islamic civilization in Egypt. This caliphate was born between two political powers, the Abbasids in Baghdad, and the Umayyad II in Cordova. Over a period of 262 years, the Fatimids have made rapid progress, especially during the time of Al-Muiz, Al-Aziz and Al-hakim. These advances cover various fields, namely: 1) Progress in trade relations with the non-Islamic world, including India and the Christian Mediterranean countries. 2) Advances in art, can be seen in a number of palace decorations and architecture. 3) In the field of knowledge with the construction of Al-Azhar University. 4) In the economic sector, both in the agricultural, trade and industrial sectors. 5) In the field of security. The collapse of the Fatimid dynasty was caused by several weaknesses that existed during his reign. These weaknesses include: 1) Fatimid politics which is harsh on the Egyptian Sunni community to adhere to and recognize Shi'a teachings. 2) The control over the Fatimid territories was weakened, 3) the economy of the people and the state was weak, 4) There was resistance from the Sunnis and Christians in Egypt. 5) The struggle for power between the Barbarians and the Turks, especially in the military field. 6) The invasion of the crusaders. And the role of the caliphate is not fully functional.